1995
DOI: 10.4319/lo.1995.40.2.0316
|View full text |Cite
|
Sign up to set email alerts
|

Settlement and transport of benthic invertebrates in an intermittent upwelling region

Abstract: We monitored settlement of sea urchins (Strongylocentrotus spp.) and crabs (primarily Cancer spp.) and concurrent physical variable:; at Bodega Marine Laboratory (BML) and Salt Point (northern California) fromApril through August 1992.lJpwelling favorable winds led to lower temperatures, higher salinities, and lower subsurface pressures at BMI,, while periods of relaxation from upwelling typically caused a lagged reversal of each of these trends. This response to relaxation was due to a combination of alongsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
175
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 47 publications
5
175
0
2
Order By: Relevance
“…Relaxation or reversals in wind stress can lead to downwelling conditions where the warmer offshore surface waters and the coastal fronts are advected back onshore, delivering entrained larval organisms to the nearshore benthic habitat (Roughgarden et al, 1988;Farrell et al, 1991). Several studies have shown that variable recruitment of coastal organisms is related to upwelling dynamics in the California region (Parrish et al, 1981;Hollowed et al, 1987;Ebert and Russell, 1988;Roughgarden et al, 1988;Larson et al, 1994;Wing et al, 1995b;Connolly et al, 2001;Broitman et al, 2005;Laidig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relaxation or reversals in wind stress can lead to downwelling conditions where the warmer offshore surface waters and the coastal fronts are advected back onshore, delivering entrained larval organisms to the nearshore benthic habitat (Roughgarden et al, 1988;Farrell et al, 1991). Several studies have shown that variable recruitment of coastal organisms is related to upwelling dynamics in the California region (Parrish et al, 1981;Hollowed et al, 1987;Ebert and Russell, 1988;Roughgarden et al, 1988;Larson et al, 1994;Wing et al, 1995b;Connolly et al, 2001;Broitman et al, 2005;Laidig et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The west coast of North America is an eastern boundary ecosystem where spatial and temporal variation in larval recruitment can be influenced by the dynamics of wind-driven coastal upwelling (Parrish et al, 1981;Mooers and Robinson, 1984;Norton, 1987;Graham et al, 1992;Wing et al, 1995b;Connolly et al, 2001). Equatorward wind stress displaces coastal surface waters offshore via Ekman transport, which are replaced by colder, nutrient rich, subsurface waters (Huyer, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These currents are usually driven by wind, which is one of the three principal agents controlling the movement of larval fish and invertebrates on the continental shelf (Epifanio and Garvine 2001). Evidence indicates that these currents might affect the recruitment of invertebrates such as crabs (Blanton et al 1995;Wing et al 1995;Shanks 1998), clams (Weissberger and Grassle 2003;Ma 2005;Shanks and Brink 2005), sea urchins (Wing et al 1995), annelids (Verdier-Bonnet et al 1997), and others, although the association with the vertical current might be weak (e.g., Shanks 1998). However, only a few studies have explained the differences found in the recruitment intensity of fish as due to upwelling or downwelling flow (Reiss and McConaugha 1999;Miller and Shanks 2005), and none of these have referred to coral-reef fishes.…”
mentioning
confidence: 99%
“…Upwelling and downwelling are characterized by flow to different (mostly opposite) directions near the bottom and at the surface. Thus, passive or nearly passive larvae that are situated at different depths might be transported to different directions (on-or offshore; Roughgarden et al 1991;Blanton et al 1995;Wing et al 1995), although there is evidence that even very weak swimming larvae will not necessarily be carried by the on-and offshore currents (Shanks and Brink 2005). However, unlike most other larvae, reef-fish larvae have well-developed swimming abilities (Stobutzki and Bellwood 1994;Stobutzki and Bellwood 1997) and hearing and olfactory senses (Sweatman 1988;Atema et al 2002;Lecchini et al 2005a) that can help them to find their settlement site while proceeding against the flow.…”
mentioning
confidence: 99%